Jamaica : Interim Staff Report Under Intensified Surveillance. (IMF Staff Country Reports; Country Report, 2005)
This paper reviews the Interim Staff Report Under Intensified Surveillance for Jamaica. Following the adverse economic impact of Hurricane Ivan, the outlook for FY 2005/06 is for a rebound in growth in the context of broad macroeconomic stability. Real GDP growth slowed, and damage to agriculture contributed to double-digit inflation in FY 2004/05. Achieving the envisaged further reduction in the public debt-to-GDP ratio to 100 percent over the next four years will be challenging and demand high fiscal discipline. The IMF staff welcomes the continuing progress toward strengthening the regulatory and supervisory framework of the financial system.